Green fashion retail - Strähle, Jochen (Springer Singapore, 2017)
This book focuses on sustainability in fashion retail, which is fast becoming the pivot point of future fashion retail strategies. Chapters in the book provide theoretical and practical insight on how going green may positively influence the strategy of fashion retailers and marketers, who have to react to the changing society and customer needs. Structured in four main parts, and based on distinct research questions, readers will be able to dig deep into the individual levers for possible adaptions. It thus provides a solid understanding on how to integrate green aspects into any fashion retailers business model.
Keywords: Fashion merchandising -- Environmental aspects.; elektronické knihy; electronic books